Pengaruh Kegiatan Literasi Melalui Read aloud Buku Bacaan Bergambar Terhadap Perkembangan Bahasa Dan Kognitif Pada Anak Kelompok B Di Taman Kanak-Kanak - Nur Asmaiyah; Mustaji Mustaji; Nurul Khotimah (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
For This research aims to examine the influence of literacy activities through reading aloud picture books on the language and cognitive development of Group B children at TK Nurul Huda Karang Sekaran Lamongan in the academic year 2023/2024. This study employs a Quasi-Experiment with a quantitative approach. The variables in this study consist of one independent variable and two dependent variables. The independent variable is literacy activities through reading aloud picture books (X), while the dependent variables are language development (Y1) and cognitive development (Y2). The sample in this study includes 30 Plus Hafidzul Qur'an TK children in the experimental group (15 children B-1 and 15 children B-2) and 30 children in the control group (15 children B-3 and 15 children B-4). The data analysis technique in this study uses parametric statistical analysis, specifically the Independent t-test. The results of the research indicate that (1) There is an influence of literacy activities through reading aloud picture books on the language development of Group B children at TK Nurul Huda Karang Sekaran Lamongan in the academic year 2023/2024, with a statistically significant value of t = -2.977 and a significance level of p = 0.004, which is less than 5%; (2) There is an influence of literacy activities through reading aloud picture books on the cognitive development of Group B children at TK Nurul Huda Karang Sekaran Lamongan in the academic year 2023/2024, with a statistically significant value of t = -3.718 and a significance level of p = 0.000, which is less than 5%. This study is expected to provide insights for teachers in developing literacy activities through reading aloud picture books, especially in the language and cognitive development of Group B children at TK Nurul Huda Karang Sekaran in Lamongan district.